Determination and identification of estrogenic compounds generated with biosynthetic enzymes using hyphenated screening assays, high resolution mass spectrometry and off-line NMR - de Vlieger, Jon S.B.; Kolkman, Ard J.; Ampt, Kirsten A.M.; Commandeur, Jan N.M.; Vermeulen, Nico P.E.; Kool, Jeroen; Wijmenga, Sybren S.; Niessen, Wilfried M.A.; Irth, Hubertus; Honing, Maarten (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2010)
This paper describes the determination and identification of active and inactive estrogenic compounds produced by biosynthetic methods. A hyphenated screening assay towards the human estrogen receptor ligand binding domain (hER)α and hERβ integrating target–ligand interactions and liquid chromatography–high resolution mass spectrometry was used. With this approach, information on both biologic activity and structure identity of compounds produced by bacterial mutants of cytochrome P450s was obtained in parallel. Initial structure identification was achieved by high resolution MS/MS, while for full structure determination, P450 incubations were scaled up and the produced entities were purified using preparative liquid chromatography with automated fraction collection. NMR spectroscopy was performed on all fractions for 3D structure analysis; this included 1D- 1H, 2D-COSY, 2D-NOESY, and 1H- 13C-HSQC experiments. This multidimensional screening approach enabled the detection of low abundant biotransformation products which were not suitable for detection in either one of its single components. In total, the analytical scale biosynthesis produced over 85 compounds from 6 different starting templates. Inter- and intra-day variation of the biochemical signals in the dual receptor affinity detection system was less than 5%. The multi-target screening approach combined with full structure characterization based on high resolution MS(/MS) and NMR spectroscopy demonstrated in this paper can generally be applied to e.g. metabolism studies and compound-library screening.